Virgibacillus ihumii sp. nov., a new bacterium isolated from the stool of healthy African children. (November 2020) - Camara, A.; Konate, S.; Lo, C.I.; Kuete, E.; Sarr, M.; Amsrtong, N.; Niare, S.; Thera, M.A.; Fenollar, F.; Raoult, D.; Million, M.
Abstract: During a case–control study on severe acute malnutrition, strain Marseille-Q1233 was isolated. It is a Gram-positive, rod-shaped and halophilic bacillus isolated from a stool sample of Malian child under the age of 5. The fatty acid profile of the strain consisted of C15:0-anteiso and C14:0-iso as major components. Digital DNA-DNA hybridization and average nucleotide identity calculation showed 23.10% and 80.81% similarity respectively between strain Marseille-Q1233 and Virgibacillus siamensis strain Marseille-P2607, the phylogenetically closely related species with standing in nomenclature. On the basis of these results, we report the description of Virgibacillus ihumii sp. nov. strain Marseille-Q1233 as a new bacterial species.